PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPAS KELAS V UNTUK MATERI MENDENGAR KARENA BUNYI - Risdawati Zulfikar; Rezki Ramdani; Kamriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Risdawati. 2024 “ The purpose of this study is to determine the level of change in learning outcomes among fifth-grade students at Labuang Baji I Public Elementary School after participating in a learning process that implements a problem-based learning model. This research uses a Classroom Action Research (CAR) model. The study was conducted in two cycles through four stages: planning, acting, observing, and reflecting. The research was carried out over a four-week period from August 8, 2024, to August 29, 2024, involving 14 fifth-grade students at Labuang Baji I Public Elementary School. During this research, the material on "Listening Because of Sound" was selected. The results show that the implementation of the problem-based learning model can improve students' learning outcomes in science education. The learning outcomes in cycle I showed an average completion rate of 43% and in cycle II of 71.42%.